2004
DOI: 10.1111/j.1365-3164.2004.411_23.x
|View full text |Cite
|
Sign up to set email alerts
|

FC‐23 
Feline plasma cell pododermatitis: a retrospective study of 26 cases

Abstract: During the last few years, reports have appeared claiming that lufenuron diminished or even cured dermatophyte infections in cats and dogs. As these observations have a rather anecdotal character leading to some ambiguity in the literature, it was decided to test lufenuron in a generally accepted animal model for dermatomycotic infection. The test was carried out in guinea pigs artificially infected with Microsporum canis on scarified dorsal skin and orally treated with lufenuron (Programä). The efficacy of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Die Ursachei st bis heute unbekannt. Glukokortikoide,D oxycyclin( 10 mg/kg KM/Tag)u nd auch chirurgischeE ingriffe werdena ls Therapiemöglichkeiten vorgeschlagen (19,39,40,84).…”
Section: Hautveränderungen Assoziiert Mithoher Rate An Felv/fiv-positunclassified
“…Die Ursachei st bis heute unbekannt. Glukokortikoide,D oxycyclin( 10 mg/kg KM/Tag)u nd auch chirurgischeE ingriffe werdena ls Therapiemöglichkeiten vorgeschlagen (19,39,40,84).…”
Section: Hautveränderungen Assoziiert Mithoher Rate An Felv/fiv-positunclassified
“…Notoedric mange is a potentially fatal syndrome of contagious dermatitis with systemic complications caused by obligately parasitic, burrowing mites of the genus Notoedres , family Sarcoptidae (Guaguere et al 1999; Scott et al 2001; Gross, 2005). These mites are closely related to mites in the genera Sarcoptes, Psoroptes, Chorioptes and Otodectes and include at least 41 named species in the genus (Klompen, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma cell pododermatitis is an uncommon disease in cats and has been described as exclusively affecting the footpads 1–7 . The aetiology is unknown, but the marked plasma cell infiltrate, consistent hypergammaglobulinaemia, and response to immuno‐modulating therapy suggest an immune‐mediated basis.…”
Section: Introductionmentioning
confidence: 99%
“…An infectious aetiology has also been suggested but has not been definitively established. There are conflicting reports regarding the involvement of feline immunodeficiency virus (FIV) 6–8 . Guaguere and Prelaud suggested that plasma cell pododermatitis is a cutaneous reaction pattern with multiple causes, including infections 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation